TECTONICS AND GEODYNAMIC EVOLUTION OF SOUTHEASTERN KAMCHATKA - Aprelkov S.Ye.; Ivanov B.V.; Popruzhenko S.V. (My University, 2001)
Characteristics are given of pre-Cenozoic and Cenozoic structural-material complexes of southeastern Kamchatka, and paleogeodynamic conditions of their formation are considered. A tectonic sketch map has been compiled of the Petropavlovsk geodynamic test area, including the water area of Avacha Bay, on the basis of complex interpretation of geological and geophysical data.
Keywords: Cenozoic; Kamchatka; Cenozoic; Кайнозой